2019
DOI: 10.1021/acsomega.9b02129
|View full text |Cite
|
Sign up to set email alerts
|

Porous Multicomponent Mn–Sn–Co Oxide Microspheres as Anodes for High-Performance Lithium-Ion Batteries

Abstract: Porous multicomponent Mn–Sn–Co oxide microspheres (MnSnO3–MC400 and MnSnO3–MC500) have been fabricated using CoSn(OH)6 nanocubes as templates via controlling pyrolysis of a CoSn(OH)6/Mn0.5Co0.5CO3 precursor at different temperatures in N2. During the pyrolysis process of CoSn(OH)6/Mn0.5Co0.5CO3 from 400 to 500 °C, the part of (Co,Mn)(Co,Mn)2O4 converts into MnCo2O4 accompanied with structural transformation. The MnSnO3–MC400 and MnSnO3–MC500 microspheres as secondary nanomaterials consist of MnSnO3, MnCo2O4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…For example, Yang et al adopted a controllable pyrolysis method of the CoSn­(OH) 6 /Mn 0.5 Co 0.5 CO 3 precursor to synthesize multicomponent Co–Sn–Mn–O anode electrodes. It delivered 952.6 mA h/g at the 2nd cycle to 145.4 mA h/g after the 160th cycle, which shows extraordinary capacity fading, showing unstable cyclic ability caused by the reactive process during cycling . In contrast, TMO@C@TMO composite with double active materials achieves large capacity as well as a long cycling life and stable cycling performance. , For instance, Guo et al reported that SnO 2 @C@VO 2 hollow nanospheres exhibited a stable specific capacity of 597.4 mA h/g at 0.5C after 100 cycles .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al adopted a controllable pyrolysis method of the CoSn­(OH) 6 /Mn 0.5 Co 0.5 CO 3 precursor to synthesize multicomponent Co–Sn–Mn–O anode electrodes. It delivered 952.6 mA h/g at the 2nd cycle to 145.4 mA h/g after the 160th cycle, which shows extraordinary capacity fading, showing unstable cyclic ability caused by the reactive process during cycling . In contrast, TMO@C@TMO composite with double active materials achieves large capacity as well as a long cycling life and stable cycling performance. , For instance, Guo et al reported that SnO 2 @C@VO 2 hollow nanospheres exhibited a stable specific capacity of 597.4 mA h/g at 0.5C after 100 cycles .…”
Section: Introductionmentioning
confidence: 99%
“…have been developed. In contrast, various high-capacity anodes, such as metal oxides, sulfides, Si, and P, have been studied, but few of them extend to commercial applications. It should be noted that for the anode, thousands of reports and papers claim that the low specific capacity (372 mAh g –1 ) of graphite anodes is the bottleneck of LIB energy density, and thus, many novel anodes with specific capacities two times (oxides and sulfides) or more than three times (Si and P composites) greater than that of graphite have been developed . Nevertheless, graphite has a 98% market share, which results from the good balance of relatively low cost, abundance, high energy and power density, and stable cycle stability.…”
mentioning
confidence: 99%
“…This cathode presented a specific capacity ( C p ) of 167 mAh g –1 and an average discharging potential (ADP) of 3.93 V vs Li/Li + . The discharge (delithiation process) profiles of graphite, P, Si, , Li 4 Ti 5 O 12 (LTO), SnO 2 , SnS 2 , and a nanocarbon (graphdiyne) are shown in Figure . It is obvious that these curves exhibit remarkably different shapes.…”
mentioning
confidence: 99%
See 2 more Smart Citations